Motorization Rate Resulting in a Road Traffic Accident an Epidemiological Audit of Injuries and Factors in the Medium-Scaled Cities of Punjab, Pakistan - Nadir Ali, Sadaf Sajid, Fatima Arshad, Usama Ahmad, Humza Naveed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Motor vehicles are increasing exponentially day by day all over the world with a global increasing prevalence of road traffic accidents. This situation of mass motorization has affected developing countries like Pakistan as well. Due to a lack of popper legislation and implementation of the law, the RTA situation is worse and requires proper research of epidemiological factors and medico-legal evaluation of injuries. Purpose: To see the pattern of RTA injuries and various epidemiological factors influencing them in the medium-scaled city like Sargodha, Gujranwala, Sialkot, and Gujarat Punjab, Pakistan. Study design: It is a retrospective study to evaluate and assess the pattern, severity, and epidemiological factors concerning RTA injuries and their medico-legal relationship during four years period from 2016 to 2019 in the medium-scaled cities of Punjab, Pakistan. Nearly 300 cases were selected to get information on predesigned Performa from Hospital records of DHQ Teaching Hospitals of Sargodha, Gujranwala, Sialkot, and Gujarat. Method and materials: After collecting data on designed Performa, the information was collected about epidemiological factors, type of injuries, the pattern of injury, outcome of injury, and medico-legal outcome for furthering justice. A descriptive statistical method was applied for the analysis and evaluation of collected data. Furthermore, standard deviation, F-statistics, and Chitest p-value were also applied to see the association of epidemiological factors with RTA injuries. Results: In a total of 300 cases of road traffic accidents, the average age was found 28.5years of age with gender male in most of the cases (86%). The 15-35 years age group was identified in more than 70 % of cases with the majority of accidents being motorcyclists with pillion riders and pedestrians. The majority of victims suffered RTA injuries while crossing the roads and constituted 30.66 % of all the cases followed by the victims passing by the side of roads with 24 %. The head and neck injuries were the most affected in most of these cases followed by extremities injuries. Conclusion: Motorcyclists with pillion riders were mostly involved in road traffic accidents. Males in the age group 20-30 years were the most affected victims being the socially active age group involved in motoring. The grievous and life-threatening injuries are increasing resulting in a very high rate of mortality and morbidity in society. The study suggests strict legislation and proper implementation of health and safety measures to avoid high RTA rates. Keywords: Motorization, RTA, automobile accidents, grievous injuries, health & safety measures.